Potentiality of Graphene Oxide and Polyoxometalate as Radionuclides Adsorbent to Restore the Environment after Fukushima Disaster: A Mini Review - Bangun Satrio Nugroho; Muh Nur Khoiru Wihadi; Fabian Grote; Siegfried Eigler; Satoru Nakashima (Indonesian Journal of Chemistry, 2021)
This paper discusses the promising candidate of excellent materials, graphene oxide (GO) and polyoxometalates (POMs), for radionuclide adsorbent. In this perspective, the unique properties of GO and POMs make them ideal candidates for developing new composites having the ability to adsorb radionuclides, and several essential things are reviewed. First, the anchoring mechanism to deposit POM on the GO surface area by (i) carboxylation method, (ii) covalent bonding, and (iii) impregnation method. Second, the radionuclides removal mechanism is described in several systems: (i) coagulation, (ii) electrostatic interaction, (iii) ion trapping, and (iv) H+-exchange. Third, the experimental condition that employed to enlarge the sorption capacity such as (i) pH adjustment, (ii) employing multiple oxidations, and (iii) cation charge. A thorough understanding of the POM-anchored GO material can pave the way for future research on similar materials. It can also help in understanding the nature of the interactive collaboration present between GO and POM.